Pengembangan Modul Kokurikuler Berbasis Sistem Among Terintegrasi Ecopreneurship untuk Memperkuat Dimensi Kemandirian Siswa Sekolah Dasar - Lina Setyawati; Yuli Prihatni; Ana Fitrotun Nisa (CV. Creative Tugu Pena, 2026)
This study aimed to develop a co-curricular module based on the Among System integrated with ecopreneurship to strengthen elementary school students' independence. The study employed a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The needs analysis was conducted in October 2025 through classroom observations and interviews at SD Negeri Minomartani 2 and SDIT Salsabila 2 Klaseman. The product was evaluated through a limited trial involving 15 fourth-grade students and a field trial involving 28 fourth-grade students. Data were collected using observations, interviews, validation sheets, response questionnaires, and independence observation sheets, and were analyzed descriptively and using the normalized gain (N-Gain) test. The findings revealed that the developed module achieved a very high level of validity based on expert and practitioner evaluations, received highly positive responses from teachers and students, and effectively strengthened students' independence with a high improvement category. The effectiveness of the module was supported by the integration of the Among System and ecopreneurship, which provided project-based learning experiences that encouraged decision-making, reflection, and responsibility. The developed module offers an alternative co-curricular learning resource to support the implementation of the Merdeka Curriculum while strengthening character education in elementary schools.